2014
DOI: 10.1109/jstqe.2013.2255587
|View full text |Cite
|
Sign up to set email alerts
|

Direct-Current and Alternating-Current Driving Si Quantum Dots-Based Light Emitting Device

Abstract: Light emitting devices based on Si quantum dots/SiO 2 multilayers with dot size of 2.5 nm have been prepared. Bright white light emission is achieved under the dc driving conditions and the turn-on voltage of the device is as low as 5 V. The frequencydependent electroluminescence intensity was observed under ac conditions of square and sinusoidal wave. It was found that the emission wavelength changes with frequency when sinusoidal ac is applied. The degradation of emission intensity is less than 12% after 3 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(1 citation statement)
references
References 24 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…A stable electroluminescence (EL) was observed at room temperature under the applied voltage higher than 17 V. The EL peak was shifted from 780 to 600 nm with decreasing the Si sublayer thickness from 4 to 1 nm [45] . Rui et al also studied the EL characteristics of Si NCs/SiC multilayers [46] . They prepared the multilayers with different dot sizes after high temperature annealing, and they found that the EL peak was blueshifted and the intensity was improved with decreasing the dot size, which proved that the EL was originated from the recombination of electron-hole pairs in Si NCs.…”
Section: Light Emitting Devicesmentioning
confidence: 99%
“…A stable electroluminescence (EL) was observed at room temperature under the applied voltage higher than 17 V. The EL peak was shifted from 780 to 600 nm with decreasing the Si sublayer thickness from 4 to 1 nm [45] . Rui et al also studied the EL characteristics of Si NCs/SiC multilayers [46] . They prepared the multilayers with different dot sizes after high temperature annealing, and they found that the EL peak was blueshifted and the intensity was improved with decreasing the dot size, which proved that the EL was originated from the recombination of electron-hole pairs in Si NCs.…”
Section: Light Emitting Devicesmentioning
confidence: 99%